Pitfalls in the diagnosis and management of aortic stenosis - Chin, Ashley; Commerford, Patrick (SA Heart Journal, 2017)
In many instances the diagnosis and management of aortic stenosis (AS) is straightforward. In others, however, the diagnosis and management of AS can be extraordinary difficult. Clinicians need to be aware of the pitfalls in diagnosis and management. Diagnosis and assessment of disease severity begins with a detailed history and physical examination. Echocardiography in experienced hands is the standard investigation of choice to confirm the diagnosis and to assess its severity. While the treatment of symptomatic severe AS is surgery, asymptomatic patients with severe aortic disease and concomitant disease, like hypertension, requires an individualised approach.